Strategi Komunikasi Pondok Pesantren dalam Dakwah Digital : Studi Kasus pada Balai Latihan Kerja Hidayatul Mubtadi-ien - Umar Biliqoillah Umar; Agi Muhammad Abdul Ghani; Aang Ridwan (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
The rapid growth of digital media has fundamentally altered how religious knowledge is acquired, evaluated, and shared in contemporary Muslim societies. Islamic boarding schools (pesantren), long recognized as centers of sanad-based scholarly transmission, now face the dual imperative of preserving religious authority while simultaneously engaging with digital communication platforms that reach younger, digitally literate audiences. This study investigates the digital da'wah communication strategy developed by Pondok Pesantren Hidayatul Mubtadi-ien in Indramayu, West Java, through its Community Work Training Center (Balai Latihan Kerja Komunitas, BLK-K). Using a qualitative case study design, data were gathered through in-depth interviews, structured observation, and institutional documentation. Analysis was guided by Thompson's E-V-R Congruence framework, which examines the alignment among organizational environment, core values, and available resources. Findings demonstrate that the pesantren constructs its digital da'wah strategy through three integrated pillars: adaptive environmental reading, value-based content governance anchored in adab, tawadhu', sanad, and Ahlussunnah wal Jama'ah principles, and the systematic mobilization of BLK-K as a digital incubation and media production hub. This research contributes a replicable institutional model for pesantren seeking to participate meaningfully in digital religious discourse without compromising scholarly integrity.